Five language style analysis of the host in the tonight show talk show: A sociolinguistics analysis - Muziatun Muziatun; Syarifuddin Achmad; Puspita Wulandari Samidu (University of Kuningan, 2020)
This thesis presents the language style used by Jimmy Fallon in The Tonight Show talk show. The objective of this study is to investigate the types of language style used by Jimmy Fallon in his talk show based on Joos’s (1967) theory. This research applied descriptive qualitative method. The data of this research were taken from the talk show video and the video transcript. The main theory which was used in this research was taken from Five O’clock book by Martin Joss (1976) and the book of An Introduction to Sociolinguistics by Janet Holmes (1992). The result of this research showed that the researcher has found 29 conversations that contain types of the language style based on Joos’s (1967) theory. As the result, it finds consultative style with 11 data and casual style with 18 data, which casual style becomes dominantly used.